Polyaniline-based nanocomposite electrode for high power output microbial fuel cells. - Miao, Jianwei. (2011)
Through years of research in the field of microbial fuel cells, researchers have found that the electrode material is one of the most important factors in affecting the overall performance of microbial fuel cells. It’s also known that the bacteria attachment, electron transfer rate and substrate oxidization efficiency are directly influenced by the anodic materials and their microstructures, so more researchers have turned to the area of anodic material development and modifications. In our project, nanostructured polyaniline-based nanocomposites were fabricated and used as the anodic materials in the microbial fuel cells. Scanning electron microscopy was employed to characterize the surface morphologies of the samples we fabricated. Electrochemical experiments, such as chronoamperometry, cyclic voltammetry and electrochemical impedance spectroscopy, were conducted to investigate the electrocatalytic behavior of the composite anodes. In this project, we found that the MFCs using polyaniline-based nanocomposites as anodic materials could generate a maximum output power density from 17.13mW/m2 to 46.73mW/m2, which was 2.67 -7.29 times higher than the maximum power density generated by the conventional carbon cloth (6.41mW/m2).